Faktor-Faktor Yang Mempengaruhi Impor Non-Migas Indonesia Kurun Waktu Tahun 1985-2012 - Pradipta, Made Adiel; Swara, I Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 8, Agustus 2015 (pp. 873-1047), 2015)
The high non-oil and gas imports that dominate Indonesia's total imports annually brings positive and negative effects for the economy. The higher non-oil imports annually weakening impact of domestic industry and the agricultural sector due to the inability of the price competition against foreign products. On the other hand the presence of non-oil imports the government is able to provide goods to support the welfare of society. This study was conducted to determine the effect simultaneously and partially between reserves, gross domestic product, US dollar exchange rate and inflation on non-oil imports over the period 1985-2012. The result showed simultaneous foreign exchange reserves, gross domestic product, US dollar exchange rate and inflation significantly to the non-oil and gas imports over the period 1985-2012. In partial reserves and gross domestic product has a positive and significant impact, while the US dollar exchange rate had a negative and significant effect, while inflation is no significant effect on non-oil imports the period 1985-2012
Keywords: Indonesian non-oil imports; foreign exchange reserves; GDP; the US dollar exchange rate; inflation.